The Greek Dialects in Old Attic Comedy - Kudulytė-Kairienė, Audronė (Literatūra, 2013)
The present article deals with the Greek dialects in Old Attic Comedy. Aristophanes is the greatest representative of this genre and the one whose complete plays have been preserved. The works of his contemporary comic poets have survived in fragments. The author of this article analyses some dialectal features of comediographs such as Apollophanes, Crates, Eupolis, Epilycus, Strattis, Aristophanes. The fragments of Old Comedy are difficult to interpret because sometimes excerpts are badly battered, the dramatic context is missing, and we do not know who is speaking the fragmentary lines that have survived. The analysis of dialectal forms shows that Greek comediographs were interested in dialects. The representation of different dialects was customary in Old Attic Comedy. Comic writers used non-Attic dialects to make their personages more realistic or to make a mock of them. Many dialectal forms in comedies contain comicality, irony, parody, intertextuality or are paratragic and might be borrowed from a tragedy, lyric or epos. In the comedies Lysistrata and Acharnians, Aristophanes reproduces Laconian, Megarian, and Boiotian speeches. He had to pick out a convincing number of the most peculiar features present to these dialects to the audience. The phonologic and morphologic features of the dialectal words in comedies generally accord with epigraphic records.